The Influence of Sharia Economic Law on the Growth of Micro, Small, and Medium Enterprises (MSMEs) in the Digital Era - Judijanto, Loso; Farid, Diana; Ali Fikri, Yudistia Teguh; Arilaha, Muhammad Asril; Syamsul, E Mulya (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aims to analyze the influence of sharia economic law on the growth of Micro, Small and Medium Enterprises (MSMEs) in the digital era. MSMEs have an important role in a country's economy, including in creating jobs, increasing people's incomes, and reducing economic disparities. However, MSMEs often face challenges in dealing with changes in the business environment, especially in the rapidly developing digital era. Therefore, it is important to analyze the influence of sharia economic law on the growth of MSMEs in the digital era. The research method used in this study is a qualitative method with a literature study approach. Data is collected from various relevant sources, such as academic journals, research reports, and related publications. The data were then analyzed using a comparative descriptive approach to identify the relationship between Islamic economic law and the growth of MSMEs in the digital era. The results of the study show that sharia economic law has a positive influence on the growth of MSMEs in the digital era. Sharia economic law provides a fair and equitable framework in economic activities, which encourages the development of MSMEs. The principles of sharia economic law, such as the prohibition of usury, speculation and unclear transactions, encourage MSMEs to adopt business practices that are more sustainable and oriented to social values. It is hoped that this research will make an important contribution in understanding the relationship between Islamic economic law and the growth of MSMEs in the digital era. The implication of this research is the importance of encouraging the adoption of sharia economic law in regulations and policies related to MSMEs in the digital era. In doing so, the government and related institutions need to consider the needs of MSMEs in facing challenges and taking advantage of opportunities that exist in the digital era, while still adhering to the principles of sharia economic law.